2020
DOI: 10.3390/w12020611
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sea Ice on the Hydrodynamics and Suspended Sediment Concentration in the Coastal Waters of Qinhuangdao, China

Abstract: The influence of sea ice on the hydrodynamics, sediment resuspension, and suspended sediment concentration (SSC) in the coastal area of Qinhuangdao was systematically investigated using 45-day in situ measurements at two stations (with ice at station M1 and without ice at station M2) in the Bohai Sea in the winter of 2018. It was found that the daily fluctuations of temperature and salinity at M1 are more significant than those at M2. During a typical seawater icing event on January 28, the temperature and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The research results demonstrated its successful use in the flow rate regulation system of the FL-12 wind tunnel's air supply, and the maximum absolute error was only 2.7 g/s. Jiang et al [80] proposed a digital valve group driven by a combination of PWM and PCM control signals. As depicted in Figure 14, the digital valve group consisted of four binary-coded digital valves and one small flow rate digital valve.…”
Section: Compound Coding Control Strategy 421 Pcm+pwmmentioning
confidence: 99%
“…The research results demonstrated its successful use in the flow rate regulation system of the FL-12 wind tunnel's air supply, and the maximum absolute error was only 2.7 g/s. Jiang et al [80] proposed a digital valve group driven by a combination of PWM and PCM control signals. As depicted in Figure 14, the digital valve group consisted of four binary-coded digital valves and one small flow rate digital valve.…”
Section: Compound Coding Control Strategy 421 Pcm+pwmmentioning
confidence: 99%
“…The changes of SSC could be represented by the changes of remote sensing reflectance of water [63,64]. The SSC in the Yellow River estuary is very high (>200 mg/L).…”
Section: Sensitive Band Of Sscmentioning
confidence: 99%